(untitled) (Research, Society and Development, 2024)
Objective: To report a clinical case of a male patient with locally invasive Squamous cell carcinoma in the lower lip region and to highlight the oncological treatment instituted. Material and methods: This is a descriptive clinical case report study of a patient treated at the Samur Hospital located in the city of Vitória da Conquista-Bahia, with information obtained from the medical records of the Samur Hospital. Case report: A 65-year-old male patient, farmer, leukoderma, smoker and chronic alcoholic, attended the dental outpatient clinic of a private hospital to start the adaptation of the oral environment prior to radiochemotherapy treatment. Extraoral physical examination revealed an ulcerative lesion with crusted areas expanding to the mental region and labial commissures. Intraoral physical examination revealed a considerable loss of tissue continuity in the region of the infernal labial mucosa. Conclusion: Thus, radiochemical and therapeutic treatment in lip cancer with locally advanced staging associated with medical and dental follow-up provides positive results. The importance of the presence of a stomatologist in the multidisciplinary hospital team is also highlighted, because, despite the difficulty for the patient to adhere to the return appointments periodically, the verbal and technical intervention helped to close the patient’s clinical condition.